Infructescence size has a larger effect than light environment on the abundance of different arthropod feeding guilds dwelling on the infructescences of a terrestrial bromeliad in a xerophytic forest. (2nd September 2017) - Montero, Guillermo; Klekailo, Graciela; Freire, Rodrigo; Torres, Patricia; Cococcioni, Andrés; Barberis, Ignacio
ABSTRACT: Bromeliads are a conspicuous feature of many Neotropical xerophytic forests. Bromelia serra is an understory bromeliad living in xerophytic forests of the Humid Chaco, which shows high phenotypic plasticity when exposed to different environmental conditions. Its infructescences carry many fleshy fruits that are colonized by arthropods from different feeding guilds. We used structural equation modeling and redundancy analysis to evaluate the influences of light environment, plant size, and infructescence size on the abundance of five different feeding guilds of arthropods dwelling on the infructescences ('fruit-secretion feeders, ' 'infructescence-detritus feeders, ' 'predators, ' 'pulp feeders' or 'seed feeders'). Plant size was negatively associated with canopy openness, whereas infructescence size was positively associated with plant size. The abundance of all feeding guilds, except fruit-secretion feeders, were positively associated with infructescence size.